2010
DOI: 10.17305/bjbms.2010.2662
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of CYP2C9*2, CYP2C19*2, and CYP2D6*4 polymorphisms in patients with type 2 diabetes mellitus

Abstract: Th is is the fi rst study performed in population from Bosnia & Herzegovina (BH), in which we analysed a signifi cance of genetic variations in drug-metabolising enzyme, cytochrome P (CYP), in pathogenesis of Type  diabetes. We have determined allele frequencies for CYPC*, CYPC*, and CYPD* in diabetic patients and nondiabetic controls. Genomic DNA was extracted from blood samples collected from  diabetic and  nondiabetic subjects. A real-time polymerase chain reaction was used for the detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 7 publications
3
16
0
Order By: Relevance
“…For the CYP2C19 gene polymorphism, only one study on the association between CYP2C19 and hypertension showed that CYP2C19*2 variants did not have any association with hypertension in a Korean population (Shin et al, 2012). Concerning diabetes mellitus, CYP2C9*2, *3, and CYP2C19*2 have been shown to have no association with diabetes mellitus (Semiz et al, 2010;Weise et al, 2010), which is consistent with our results. One study even showed that individuals with the CYP2C19*2 variant seem to protect against metabolic syndrome (Gaio et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…For the CYP2C19 gene polymorphism, only one study on the association between CYP2C19 and hypertension showed that CYP2C19*2 variants did not have any association with hypertension in a Korean population (Shin et al, 2012). Concerning diabetes mellitus, CYP2C9*2, *3, and CYP2C19*2 have been shown to have no association with diabetes mellitus (Semiz et al, 2010;Weise et al, 2010), which is consistent with our results. One study even showed that individuals with the CYP2C19*2 variant seem to protect against metabolic syndrome (Gaio et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, Semiz et al38 reported that no significant difference in allele frequencies for CYP2C9 * 2 , was demonstrated between diabetic and non-diabetic subjects. Recently, Kaur-Knudsen et al39 reported the findings of large studies on the association between genetic variation in CYP 1B1 and CYP2C9 and the risk of disease, and rebutted the hypotheses that these genetic variants?influenced the risk of tobacco-related cancer, female cancer (as cervical and endometrial cancers), chronic obstructive pulmonary disease, and ischemic vascular disease.…”
Section: Discussionmentioning
confidence: 92%
“…Significant interethnic differences in the distribution of allele frequencies rs776746*G and rs776746*A was observed (Table 3) [6,21,25,36,[44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63]. The rs776746*G allele is common in European popula tions and less common in Asian populations, and a significantly lower number of cases was observed in black populations.…”
Section: Resultsmentioning
confidence: 99%